Immunohistochemical expression of human epididymis 4 in ovarian malignancy - Nahar, Begum Afrin; Saha, Rama; Das, Chhanda; Kamilya, Gourishankar (International Journal of Research in Medical Sciences, 2019)
Background: Ovarian malignancies has the highest mortality rate among all gynaecological malignancies. Surface epithelial tumors form two thirds of all ovarian neoplasm and 90% of all ovarian cancers are surface epithelial carcinomas. Mortality in case of ovarian malignancy is high due to late diagnosis. Early and accurate diagnosis can improve the case specific management. HE4 (Human Epididymis Protein 4) which is proved to be overexpressed in the ovarian cancer cells, is considered a new biomarker for ovarian cancer diagnosis which helps in early diagnosis and patient management. Aims and objectives of the study was to evaluate the immunohistochemical expression of HE4 in various ovarian malignancies. Methods: It was a cross sectional, prospective, single institution-based study, conducted in the department of Pathology in collaboration with the Department of Gynaecology and Obstetrics, from December 2016 to January 2019 in institution. A total 74 ovarian malignancies were selected for this study. Results: Serous carcinoma was the most common ovarian malignancy followed by endometrioid carcinoma. Highest percentage of expression of HE4 was seen in high grade serous cancer and malignant endometrioid tumor. Conclusions: HE4 was highly expressed in malignant ovarian tumour especially serous and endometrioid carcinoma and can be used as an important biomarker for malignant ovarian neoplasm. Expression in high grade ovarian serous cancer support its prognostic value also.